Order books, markets and convex analysis. (3rd August 2017) - Flåm, Sjur Didrik
Abstract: This paper considers how an order market might evolve over a fairly short period – say, during a day. It uses elementary convex analysis to model agents' choice of prudent orders, and it explores whether equilibrium is attainable.